The Development of Discovery Learning Assisted by Geogebra and Assemblr Edu Application to Increase Juinor High School Students’ Understanding Ability on Geometry - Raden Astri Prasetiawati; Wahyu Hidayat; Heris Hendriana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Mathematics is a subject that has an important role in human life. The goal of learning mathematics at school is an understanding of mathematical concepts. Students must have an understanding of mathematical concepts after the mathematics learning process takes place. Students who have an understanding of mathematical concepts will be able to explain related concepts and apply them. This study aims to develop a discovery-based method of learning using Geogebra and Assemblr Edu applications to understand geometric concepts in junior high school students. This study uses the Multimedia Development Life Cycle (MDLC) model. Data collection was carried out by means of interviews and questionnaires. Media validation is based on material review experts and media experts. Data analysis technique by conducting qualitative descriptive analysis based on the validation of material experts and media experts. The average percentage score from material experts is 94.7% and the average percentage score from media experts is 95.8% indicating that the development of discovery-based method learning using the Geogebra and Assemblr Edu applications is feasible to use as an alternative solution to understanding geometry concepts in junior high school students. The author suggests that the learning media that has been designed can be tested on class IX junior high school students so that it can be useful for students to understand Geometry material. And in addition, further research can be carried out to determine the effectiveness of the learning media that have been made.